REAL-TIME ATTENDANCE AND DISCIPLINE MONITORING THROUGH EVOCARD - Inayah, Shorihatul; Mabruri, Ahmad Hudan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
EvoCard is an attendance and discipline monitoring system that uses real-time technology to increase efficiency and accuracy in recording attendance at various institutions, including Madrasah Aliyah Negeri 1 Tuban, East Java. This research aims to evaluate the effectiveness of EvoCard in improving individual attendance and discipline through the automatic collection and analysis of recorded data. Data shows a significant increase in average attendance and a decrease in tardiness rates after implementing EvoCard. Apart from that, the positive response from users, both students, teachers, staff, employees and parents, shows that this system is able to discipline encourage and responsibility. EvoCard also reduces administrative workload by providing fast and transparent access to attendance data. The results of this research indicate that EvoCard is an effective tool in monitoring and improving attendance and discipline and provides significant benefits for institutions that adopt it.